Using financial resources in budgetary institutions: advanced accounting techniques - Struk, N. S.; Rak, G. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
Accounting techniques, methods and procedures set in the necessary sequence form the accounting process, and they are fixed in the accounting policy at companies, institutions and organizations. The volatility of the legal framework pertaining to accounting procedures and accounting methods causes the need for new scientific developments in this field and their applications in the accounting practices of business entities. The article’s objective is to reveal the specifics involved in applications of existing ac- counting techniques for recording financial flows in government institutions, and to show the relationship between accounting principles and accounting methods. This objective is achieved by solving the following problems: to reveal the content of the accounting process and its technical components; to analyze the procedural-additive approach to substantiating the essence of accounting techniques; to describe accounting techniques used for recording of financial flows in government institutions; to systematize and compare Ukrainian studies on accounting principles and accounting techniques with analogous foreign studies, to find out the scopes of adaptation of the Ukrainian law to international standards of accounting and reporting. The study shows that accounting techniques used in Ukraine differ from international ones where traditional accounting components have stronger analytical, statistical and econometric focus. From the comparative analysis it follows that the Ukrainian law over- looks international accounting principles of reliability and accuracy, imparity, clearness and intelligibility, relevance and uniqueness. However, these principles and techniques cannot be deemed fully applicable in the Ukrainian accounting practices unless they are scrutinized in view of the specifics involved in the Ukrainian law, economic process in Ukraine, information systems and technologies used in domestic practices of accounting. The outlined specifics of the existing accounting techniques and relationships between accounting principles and accounting methods enable to propose the procedural-additive approach to accounting techniques used to record financial flows in government institutions, laying grounds for further improvements in the theoretical framework for accounting in government institutions.